Recent Developments in Non-conventional Welding of Materials - Leal, Rui Manuel; Galvão, Ivan (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Welding is a technological field that has some of the greatest impact on many industries, such as automotive, aerospace, energy production, electronics, the health sector, etc. Welding technologies are currently used to connect the most diverse materials, from metallic alloys to polymers, composites, or even biological tissues. Despite the relevance and wide application of traditional welding technologies, these processes do not meet the demanding requirements of some industries. This has driven strong research efforts in the field of non-conventional welding processes. This Special Issue presents a sample of the most recent developments in the non-conventional welding of materials, which will drive the design of future industrial solutions with increased efficiency and sustainability.